EKSPLORASI STRUKTUR KEPEMILIKAN SAHAM PUBLIK DI INDONESIA TAHUN 2004 - 2008 - Nendy Pramita Shinta; Nurmala Ahmar (Universitas Hayam Wuruk Perbanas, 2011)
It is assumed that the ownership structure reflects the proportion of right principal (owner).The purpose of this study is to explore the structure of shareholding companies listed inIndonesia Stock Exchange (ISE) during 2004 and 2008. Ownership structures are classifiedinto five ownership structures of managerial ownership, institutional ownership, individualownership, public ownership and government ownership. This study explores and analyzesthe five classifications of ownership structure, namely managerial ownership, institutionalownership, individual ownership, public ownership, and government ownership in publiccompanies listed in the Indonesian Capital Market Directory (ICMD). In 2004, there were330 public companies, in 2005 there were 339 public companies, in 2006 there were 343public companies, in 2007, 393 companies, and in 2008’ 397 public companies. Testing andanalysis used in this research is descriptive ANOVA test device, using the analyticalapproach and method of content interpretative analysis.